A5 8 In Hot Water - Matkin, Eleanor; Morriss, Luke; Shkullaku, Marin (Physics Special Topics, 2023)
This paper compares different methods for producing enough energy for every household in the United Kingdom to boil a kettle at the same time. We found that the amount of CO2 that would be produced from burning coal to achieve this would be 2.32×10^6 kg. Another method would be to provide 1.71×10^8 solar panels.